Sistemsko projektiranje in konstruiranje: univerzitetni učbenik - Pehan, Stanislav; Glodež, Srečko (University of Maribor Press, 2018)
Systematic dimensioning and design: University Textbook. The university textbook covers the modern systematic approaches for dimensioning and design of machine parts and structural elements. The main difference between dimensioning and design is explained with special attention to the development process and costs of treated product. The main part of the textbook explains the methods of advanced design with consideration of design for reliability and optimisation methods. Furthermore, the practical guidelines for proper choice of materials and typical characteristics of different energetic systems are provided. The basic principles of bionics and its application in designing engineering products are also described. The textbook is primary intended for students of mechanical engineering to support the subject Systematic dimensioning and design. However, the textbook can also be used for other subjects related to the engineering design. Many practical examples included in the textbook could be helpful also for development engineers and designers in solving the real engineering problems in companies.